2017
DOI: 10.1002/ange.201610619
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of CH3NH3PbBr3 Nanoplatelets with Polarized Emission through Self‐Organization

Abstract: We report a combined experimental and theoretical study of the synthesis of CH3NH3PbBr3 nanoplatelets through self‐organization. Shape transformation from spherical nanodots to square or rectangular nanoplatelets can be achieved by keeping the preformed colloidal nanocrystals at a high concentration (3.5 mg mL−1) for 3 days, or combining the synthesis of nanodots with self‐organization. The average thickness of the resulting CH3NH3PbBr3 nanoplatelets is similar to the size of the original nanoparticles, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…38 Although no polar solvent was involved, the MAPbX 3 PNCs still decomposed or aggregated in weeks, similar to MAPbX 3 PNCs prepared via an emulsion method. 41 This shows that organic− inorganic hybrid MAPbX 3 perovskites are much more labile than those of all inorganic CsPbX 3 due to the lower formation energy of MAPbX 3 and volatile constituents like CH 3 NH 2 and HX. 41 As ternary compounds, MAPbX 3 and CsPbX 3 are usually prepared with two precursors such as MABr/CsBr/Cs oleate + PbBr 2 , which limits the variation of composition to some degree.…”
Section: Synthesis and Structural And Opticalmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Although no polar solvent was involved, the MAPbX 3 PNCs still decomposed or aggregated in weeks, similar to MAPbX 3 PNCs prepared via an emulsion method. 41 This shows that organic− inorganic hybrid MAPbX 3 perovskites are much more labile than those of all inorganic CsPbX 3 due to the lower formation energy of MAPbX 3 and volatile constituents like CH 3 NH 2 and HX. 41 As ternary compounds, MAPbX 3 and CsPbX 3 are usually prepared with two precursors such as MABr/CsBr/Cs oleate + PbBr 2 , which limits the variation of composition to some degree.…”
Section: Synthesis and Structural And Opticalmentioning
confidence: 99%
“…41 This shows that organic− inorganic hybrid MAPbX 3 perovskites are much more labile than those of all inorganic CsPbX 3 due to the lower formation energy of MAPbX 3 and volatile constituents like CH 3 NH 2 and HX. 41 As ternary compounds, MAPbX 3 and CsPbX 3 are usually prepared with two precursors such as MABr/CsBr/Cs oleate + PbBr 2 , which limits the variation of composition to some degree. On the basis of the method proposed by Wei et al, 42 Imran et al demonstrated an alternative "three-precursors approach" (Figure 1e) in which CH 3 NH 3 + and Pb 2+ were dissolved in fatty acid, followed by the injection of a benzoyl halide precursor.…”
Section: Synthesis and Structural And Opticalmentioning
confidence: 99%
“…The cubic phase at room temperature was confirmed for these nanoparticles by high-resolution TEM (HRTEM) and X-ray diffraction (XRD) characterization, as shown in Figure 2, which coincides with the reported results. 33,35 In Figure 2, both the blue-and green-CH 3 NH 3 PbBr 3 NCs show main diffraction peaks of (100), ( 110), ( 200), ( 210), (220), and (300) at 15.04°, 21.29°, 30.26°, 33.92°, 43.30°, and 45.98°, respectively, which can be well matched with the corresponding bulk CH 3 NH 3 PbBr 3 in the cubic phase (Pm3m). 36 The high-resolution TEM images of the blue-and green-CH 3 NH 3 PbBr 3 NC in Figure 2 show the interplanar distance of 2.93 and 2.10 Å, which is consistent with the ( 200) and ( 220) perovskite crystal facets, respectively.…”
mentioning
confidence: 99%
“…In another report, Liu et al showed that when a highly concentrated dispersion of spherical MAPbBr 3 NPs is stored for 3 days, nanoplates (NPLs) of MAPbBr 3 are formed due to fusion processes among the spherical NPs. 9 Moreover, because of the fusion processes, the length and the width of the NPLs cannot be controlled. Similarly, Teunis et al reported the formation of MAPbBr 3 nanowires as a result of fusion processes among spherical NPs.…”
mentioning
confidence: 99%